Exploring Learning Needs for Developing a STEAM-Oriented Differentiated Virtual Laboratory in Electroplating and Electropolishing - Rizka Fauzia Hanif; Sri Mulyani; Suryadi Budi Utomo (Universitas Sebelas Maret, 2026)
This study aims to explore the need for virtual laboratory media (V-Lab) that integrates differentiated learning using the STEAM approach for electroplating and electropolishing. The research method used is qualitative-descriptive, with the research subjects comprising 3 teachers and 75 students from two public senior high schools and one vocational high school in Metro City, Lampung. Data collection used questionnaires, learning observations, and interviews. The results of the observations show that chemistry learning is still dominated by lectures and exercises (40%), while limited equipment, materials, and costs, as well as the risk of hazardous waste, continue to limit practical activities. Students experience significant difficulties in visualizing sub-microscopic phenomena, especially in determining ion flow (74%) and reactions at the anode-cathode (62%), resulting in a low ability to calculate Faraday's Law (60%). Cognitive data analysis shows a diversity of student abilities, with the majority being at the